TINGKAT POTENSI OBJEK WISATA ALAM DI KOTA SORONG - Andri Krisno Marau; H W Wiranegara; Herika M. Taki (Universitas Trisakti, 2022)
Information on the city tourism potential is important in city development so that the contribution of the tourism sector is clear. Sorong City is the second largest city on the island of Papua which is very strategically located and has several natural tourist objects but its potential is unknown. This study aims to identify potential tourist objects in Sorong City. This study uses a quantitative approach. The potential for tourism objects is viewed from the aspects of tourist attraction, accommodation, facilities and infrastructure, and accessibility. Analysis of the potential for tourism objects uses assessment criteria based on the Guidelines for Analysis of Operational Areas for Natural Tourism Objects and Attractions (ADO – ODTWA). The results of the study show that the potential for natural tourism objects in Sorong City is at a potential level to be developed according to these guidelines.